Selection 1. (Knokke-Heist : Christian Fayt Art Gallery, 1978)
Alechinsky, Pierre ; Appel, Karel ; Bonnard, Pierre ; Botero, Fernando ; Brauner, Victor ; Chagall, Marc ; Veira da Silva, Maria Elena ; Delvaux, Paul ; De Vlaminck, Maurice ; Dufy, Maurice ; Ernst, Max ; Foujita, Tsuguhero ; Gauguin, Paul ; Kisling, Moïse ; Laurencin, Marie ; etc.
Selection, Christian Fayt Art Gallery, Knokke-Heist, 3.6. - 18.7.1978
boek